Analisis Penerapan PSAK 109 Dan PSAK 101 Penyajian Pelaporan Keuangan Akuntansi Zakat Dan Infaq/Sedekah Pada Lazismu Kl Ummi Dan Lazismu Kl Aisyiyah - Al Fianty, Amelia; Kartini, Tina; Noor, Iqbal (Expensive: Jurnal Akuntansi dan Keuangan, 2023)
This research was made to find out how the application of the Sharia Financial Accounting Standards Statement (PSAK) No. 109 and 101 regarding the presentation of the financial reports of LazisMu KL UMMI and LazisMu KL Aisyiyah, as well as knowing the obstacles in compiling the financial reports that have been made. This study used a qualitative research method with a descriptive approach. The variable used in this study is where the social situation in this study consists of three elements, namely places, people and activities. The technique used in data collection is the triangulation technique, which includes observation, interviews and documentation. With data analysis techniques performed include data reduction, data presentation, and drawing conclusions.The results of this study indicate that LazisMu KL UMMI and LazisMu KL Aisyiyah have implemented Zakat, Infak/Shadaqah Accounting in accordance with the Statement of Financial Accounting Standards (PSAK) 109. However, the disclosures are not appropriate, because notes to financial statements have not been made. In addition, the financial reports prepared by LazisMu KL UMMI are in accordance with Statement of Financial Accounting Standards (PSAK) 101, while LazisMu KL Aisyiyah is not yet in accordance with PSAK 101 concerning the presentation of financial reporting.